Design of the INARA (Inclusive and Gender Responsive Historia) Application: Accentuating Inclusive and Gender-Responsive History Learning - Khoeronisa, Kemala; Wahid, Uswanur Rachman F.; Bashori, Muzakki; Siregar, Vriska Nanda Putri (Historia Pedagogia, 2023)
This article aims to elaborate on the initial development of the historical learning application design, INARA (Inclusive and Gender Responsive Historia). The authors gathered data from literature reviews, including journal articles and online media, which were analyzed using a SWOT approach. The study's results showcase examples of inclusive and gender-responsive features in this application, such as games, quizzes, QR codes, and comics focusing on female heroes in Indonesia. The application is also designed with specific features to support differently-abled students in learning history. It is hoped that INARA can become a creative, engaging, and critical medium for history learning at school levels. Its innovative design and inclusive features make a valuable contribution to the scholarly discourse in education. This article is expected to enrich the understanding of utilizing technology to support inclusive and gender-responsive history learning. As part of further development efforts, INARA is anticipated to become a progressive educational solution supporting various learning needs. Keywords: history, application, learning, inclusive, gender responsive